Pengaruh Kompensasi, Kompetensi dan Komitmen Organisasi terhadap Kinerja Pegawai - M Adhitya Ramadhan; Muhammad Masreal Ma'ruf; Irwan Irwan; Sukiyem Sukiyem; Rizky Syahrianto Yunus Helmy NST; Sri Gustina Pane (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to determine the effect both jointly and partially between compensation, competence and organizational commitment on employee performance at the Regional Secretariat of Deli Serdang Regency. This study uses quantitative methods with the type of explanatory research using primary data and secondary data. The population in this study were employees at the Regional Secretariat of Deli Serdang Regency and as many as 65 employees were used as research samples. The data analysis technique used is multiple and partial linear regression using SPSS 24.0. The results of the regression analysis showed that of the three independent variables included in the regression model (compensation, competence and organizational commitment). The compensation variable is significant at 0.002, so it can be concluded that performance is influenced by compensation (hypothesis 1 is accepted). The competency variable has a significant value of 0.002, so it can be concluded that competence has an effect on performance (hypothesis 2 is accepted). Organizational commitment variable which has a significant value is 0.807. So it can be concluded that organizational commitment has no effect on employee performance (hypothesis 3 is rejected). The results showed that the variables of compensation, competence and organizational commitment together had a positive effect on employee performance. This is evidenced by the statistical results of the regression test obtained a value with a probability smaller than (α = 0.05), it can be explained that compensation, competence and organizational commitment have a positive effect on employee performance. Then the fourth hypothesis is accepted.